2018
DOI: 10.1038/s41598-018-30604-5
|View full text |Cite
|
Sign up to set email alerts
|

A peculiar case of Campylobacter jejuni attenuated aspartate chemosensory mutant, able to cause pathology and inflammation in avian and murine model animals

Abstract: An attenuated Campylobacter jejuni aspartate chemoreceptor ccaA mutant caused gross pathological changes despite reduced colonisation ability in animal models. In chickens, the pathological changes included connective tissue and thickening of the mesenteric fat, as well as the disintegration of the villus tips in the large intestine, whereas in mice, hepatomegaly occurred between 48–72 hours post infection and persisted for the six days of the time course. In addition, there was a significant change in the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Both proteins were found to bind aspartate with high preference, and the obtained dissociation constants are very similar to those obtained in this study for PsPto-PscA (71–73). Tlp1 (renamed CcaA) of the human pathogen Campylobacter pylori is an aspartate-specific chemoreceptor (46, 74) and was found to play an important role in virulence since experimentation with the mutant strain in different hosts resulted in a number of pathological changes in infection experiments (75). Although the corresponding molecular mechanisms remain unclear, these data underline the importance of signaling mediated by aspartate-specific chemoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Both proteins were found to bind aspartate with high preference, and the obtained dissociation constants are very similar to those obtained in this study for PsPto-PscA (71–73). Tlp1 (renamed CcaA) of the human pathogen Campylobacter pylori is an aspartate-specific chemoreceptor (46, 74) and was found to play an important role in virulence since experimentation with the mutant strain in different hosts resulted in a number of pathological changes in infection experiments (75). Although the corresponding molecular mechanisms remain unclear, these data underline the importance of signaling mediated by aspartate-specific chemoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…C. jejuni infections can occur via various routes such as through direct contact with companion and farm animals or through waterborne or foodborne transmission (Domingues et al., 2012). C. jejuni is a commensal bacterial of chickens which inhabit the chicken intestines at a level >106–108 CFU/g of chicken faeces (Oh et al., 2018) and chickens are the main vector for human campylobacteriosis (Hartley-Tassell et al., 2018). C. jejuni consist of two subspecies; C. jejuni subsp.…”
Section: Main Textmentioning
confidence: 99%
“…Previous studies have indicated that the tlp1 gene is strongly upregulated in C. jejuni strains that are colonized in chickens ( 27 ). It may also be involved in the ability of C. jejuni to attach to human intestinal cells in culture ( 28 , 29 ). The tlp1 -isogenic knockout strains had significantly reduced abilities to colonize avian and mammalian hosts, as demonstrated using chicken and mouse models ( 24 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…It may also be involved in the ability of C. jejuni to attach to human intestinal cells in culture ( 28 , 29 ). The tlp1 -isogenic knockout strains had significantly reduced abilities to colonize avian and mammalian hosts, as demonstrated using chicken and mouse models ( 24 , 28 ). However, as the natural ligand of Tlp1 is still unknown, the link between chemotaxis via Tlp1 and physiological functions has not been demonstrated until now.…”
Section: Introductionmentioning
confidence: 99%